Al-Ḥājah al-‘Ilmiyyah ilā Mawsū‘ah Ḥadīthiah Mu‘āṣarah - Naseh Uluan., Amar Abdullah (Jurnal Usuluddin, 2016)
This article presents a scientific project needed by Muslims more than many frequent encyclopedias of Islamic jurisprudence (fiqh). The huge technological development in the search of information will help in citing the references of hadith in regard to the chain of narrators and the text of the hadith; and will help in working out the greater objective commonality of hadith and Quranic verses and at the lower level will help in developing the objectivity among the hadith. The proposed encyclopedia would be devised by the elite of scholars of fiqh and hadith so it can receive acceptance by the majority of Muslims, and it will carry the features of scientific methodology which are missing in the old and new collections of hadith.